The 1:1 Division of Inheritance Between Sons and Daughters in Islamic Law: Legal, Rights and Obligations, Historical, and Sociological Perspectives - Titania Mukti; Teguh Putra Pratama (CV. FOUNDAE, 2026)
This study aims to analyze the determination of a 1:1 inheritance distribution between male and female heirs in Islamic law from the perspectives of formal juridical aspects, rights and obligations, historical aspects, and sociological aspects. The research employs a normative legal or dogmatic legal approach. The results of this study indicate that a 1:1 inheritance distribution between sons and daughters may be implemented when there is mutual consent among the heirs, even though Article 176 of the Compilation of Islamic Law and Qur'an Surah An-Nisa verse 11 explicitly stipulate that the inheritance ratio between male and female children is 2:1. This determination is based on several perspectives. First, the formal juridical perspective, which considers that men and women possess equal standing before the law in modern society. Second, the perspective of rights and obligations, which views inheritance as a right rather than an obligation, thereby allowing an equal 1:1 inheritance agreement. Third, the historical perspective, which understands the 2:1 inheritance provision as originating within the context of pre-Islamic Arab society that previously denied inheritance rights to women, making the primary principle the recognition of women as legal heirs. Fourth, the sociological perspective, which shows that daughters often provide greater care to the deceased during illness and until death, so that a 1:1 distribution is considered more reflective of justices